2019
DOI: 10.1038/s41436-018-0351-7
|View full text |Cite
|
Sign up to set email alerts
|

Haploseek: a 24-hour all-in-one method for preimplantation genetic diagnosis (PGD) of monogenic disease and aneuploidy

Abstract: Purpose: To develop an economical, user-friendly, and accurate all-in-one next-generation sequencing (NGS)-based workflow for single-cell gene variant detection combined with comprehensive chromosome screening in a 24-hour workflow protocol. Methods: We subjected single lymphoblast cells or blastomere/ blastocyst biopsies from four different families to low coverage (0.3×-1.4×) genome sequencing. We combined copy-number variant (CNV) detection and whole-genome haplotype phase prediction via Haploseek, a novel,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 19 publications
0
55
0
Order By: Relevance
“…The conclusion of this study was that robust identification of CNVs was highly feasible with low-coverage WGS 43 . In another study, low-coverage WGS also found successful application in preimplantation genetic diagnosis of monogenic disease 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion of this study was that robust identification of CNVs was highly feasible with low-coverage WGS 43 . In another study, low-coverage WGS also found successful application in preimplantation genetic diagnosis of monogenic disease 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, low-coverage WGS also found successful application in preimplantation genetic diagnosis of monogenic disease 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Both SNP arrays and NGS maximize the genetic information available from each embryo with also reference to chromosome copy number in the context of PGT-A [51]. In earlier applications, the testing of two different biopsies was performed to enable PGT-M with aneuploidy screening but, more recently, this has been achieved from the same biopsy and whole genome amplification product (WGA) in family-specific or universal protocols, improving pregnancy rates [52]. The combination of PGT-M with HLA typing and aneuploidy screening was performed in a study using WGA that was followed by aCGH and multiplex PCR from different portions of the same WGA product.…”
Section: Overview Of Pgt-hla Methodologymentioning
confidence: 99%